THE INFLUENCE OF EMPATHETICAL LEADERSHIP ON INNOVATIVE WORK BEHAVIOR: THE MEDIATING ROLE OF PSYCHOLOGICAL SAFETY AMONG EMPLOYEES OF PT BPD KALTIM KALTARA TANA PASER BRANCH - Dhea Revina Shabila; Irsan Tricahyadinata; Dwi Martiyanti (RADJA PUBLIKA, 2026)
The rapid transformation of the banking industry driven by digitalization requires organizations to enhance employees' innovative work behavior as a key source of competitive advantage. However, innovative work behavior is influenced not only by individual competence but also by leadership practices and employees' psychological conditions in the workplace. This study aims to examine the effect of empathetic leadership on innovative work behavior through the mediating role of psychological safety among employees of PT BPD Kaltim Kaltara Tana Paser Branch. A quantitative explanatory research design was employed, with data collected from 117 employees using a total sampling technique. The data were analyzed using Structural Equation Modeling–Partial Least Squares (SEM-PLS) with SmartPLS 4. The findings indicate that empathetic leadership has a positive and significant effect on both psychological safety and innovative work behavior. Psychological safety also has a positive and significant effect on innovative work behavior. Furthermore, psychological safety partially mediates the relationship between empathetic leadership and innovative work behavior. These findings suggest that leaders who demonstrate empathy by understanding employees' emotional needs can foster a psychologically safe work environment that encourages employees to express ideas, take initiative, and engage in innovative behaviors. This study contributes to the growing literature on empathetic leadership and psychological safety within the context of regional banking institutions and provides practical insights for organizations seeking to strengthen employee innovation through people-centered leadership.